PENGARUH KEPEMIMPINAN, MUTASI DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI PADA KANTOR PELAYANAN PAJAK PRATAMA BANTUL - Fachrudin , Much; Assery, Syeh (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2024)
The problem in this study is that the performance of employees has not been maximized, which can be seen from the non-achievement of the tax revenue target at the Bantul Primary Tax Service Office (KPP) in 2019 to 2021 (especially the achievement of the Account Representative target in 2021). This study aims to analyze the effect of Leadership, Mutation and Work Environment on Employee Performance at KPP Pratama Bantul. The population in this study were all employees who were still actively working at the Bantul Primary Tax Service Office, totaling 94 employees. The sample in this study (purposive sampling) is Account Representative employees, namely employees with the main task and function of collecting tax revenue. The data used in this study are quantitative data types that can be measured or calculated directly. This study uses data analysis techniques in the form of statistical calculations using SPSS software. The results of this study indicate that Leadership, Mutation and Work Environment have a positive and significant influence on employee performance at KPP Pratama Bantul. The results of hypothesis testing show that the three independent variables have a positive and significant effect on the independent variable. The greater the Leadership, Mutation and Work Environment provided by the Organization, the more employee performance will increase.